Classification of Jades (Giok) Beutong Aceh based on Mineral Composition - Nurul Aflah; Muchlis Muchlis; Khairul Halimi; Hayatun Nufus; Zoraya Maysura; M. Zuhri Simatupang (Jurnal Natural, 2014)
Beutong is a commercial origin of various kinds of Jade (Giok) in Aceh Province. From the geological view the formation of jade is due to the mélange zone. The zone is usually an assemblage of a variety mineral composition. The paragenetic minerals of the jade can be divided into four categories, which are Jadeite, Nephrite, Serpentine and Vesuvianit. The characteristics of the color were associated with a variety of constituent minerals which can be red, yellow, brown, gray, and black. Thus, by this paper we classified the jades based on their mineral constituents.